Internship on (Ni0.4Cu0.15Zn0.45)1-xMnxFe2O4 sample preparation and calcination - Mridula, Zarrin Tasnim (BRAC Univeristy, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Applied Physics and Electronics, 2017.